Translation of a Brazilian educational booklet concerning hydrocephalus into Spanish as spoken in Spain - Garcia de Avila, Marla Andréia [UNESP]; Rodríguez González, Raquel; Negrão Moreira, Karen [UNESP]; de Godoy, Ilda [UNESP]; Tavares, Paloma de Aro Jorge [UNESP]; Lira, Carlos Cézar Sousa de [UNESP]; Ferreira, Ana Silvia Sartori Barraviera Seabra [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP] (Elsevier, 2020)
Purpose: A booklet for children with hydrocephalus and their parents was presented. This study translated the Brazilian version of the booklet “Laura's diary: knowing hydrocephalus and its treatment” into Spanish as spoken in Spain. Methodology: This methodological study conducted in Spain (Universidad de Santiago de Compostela) and Brazil (Botucatu Medical School) undertook the following translation steps: translation, using two Brazilian translators fluent in Spanish; synthesis, involving a Spanish nurse with experience in education; and back-translation, using a Brazilian translator and nurse fluent in Spanish. Findings: The two versions of the initial translation were similar, with few amendments necessary during the consensus meeting between the researchers to achieve synthesis of the translations. The two versions of the back-translation were very similar to the original. Conclusion: A free Spanish booklet was presented to minimize the negative effects of surgery, empower families, and aid future research between Brazil and Spain. Mismanagement of a disease can affect a child's quality of life. Communication is essential for health education to help ensure greater participation of patients and families in care plans.
Traducción de un folleto educativo brasileño acerca de la hidrocefalia a español de España
Keywords: Children; Health education; Hydrocephalus; Rehabilitation nursing